Educating liberty democracy and aristocracy in J.S. Mill's political thought - Barker, Chris (Christopher James) (University of Rochester Press, 2018)
A comprehensive study of Mill's theory of liberty, uncovering Mill's solution to the problem of democracy, the tyranny of the majority.